2014
DOI: 10.1175/jcli-d-13-00554.1
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean Dipole Overrides ENSO’s Influence on Cool Season Rainfall across the Eastern Seaboard of Australia

Abstract: The strong relationship between eastern Australian winter–spring rainfall and tropical modes of variability such as the El Niño–Southern Oscillation (ENSO) does not extend to the heavily populated coastal strip east of the Great Dividing Range in southeast Australia, where correlations between rainfall and Niño-3.4 are insignificant during June–October. The Indian Ocean dipole (IOD) is found to have a strong influence on zonal wind flow during the winter and spring months, with positive IOD increasing both ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 24 publications
5
63
0
Order By: Relevance
“…11) in the CR ensemble mean, and in years 0 and 2 in the 2 × G ensemble mean. This could be due to the positive precipitation anomalies that can be generated by combined El Niño and pIOD events in the NW Australian region (Meyers et al, 2007;Pepler et al, 2014), which enhance the precipitation surplus caused by volcanic aerosols.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11) in the CR ensemble mean, and in years 0 and 2 in the 2 × G ensemble mean. This could be due to the positive precipitation anomalies that can be generated by combined El Niño and pIOD events in the NW Australian region (Meyers et al, 2007;Pepler et al, 2014), which enhance the precipitation surplus caused by volcanic aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…Preconditioning does impact the severity of the ENSO response. Predybaylo et al (2017) found that years with an initial central Pacific ENSO phase show the largest statistical impact from Pinatubo-sized eruptions, and that summer eruptions coincided with a more pronounced El Niño response.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations